The use of 'prince system' in minimizing the environmental damages in mining activities - Ibrahim, Mansor (Penerbit UTM Press, 1992)
PRINCE System is a method which can be applied to solve any environmental problem. An issue on reclamation policy of the ex-mining lands is cited as an example in explaining the system which has been used by Machiavelli and other politicians. There are at least four groups involved in determining the reclamation policy of the ex-mining lands; the politicians, the Department of Environment (DOE), the Chamber of Mines (COM) and the non-government organization (NGO). The proponents and the opponents of the reclamation policy can be gauged by applying the PRINCE System. Once the roots of the problems are identified, the issue can be conveniently resolved.